Data Collection on MSME Creative Industries in Medan City According to a Sharia Accounting Perspective - Kasolati, K.; Kamilah, K. (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Increasing creative industries in small and medium businesses in Medan is the main focus in efforts to revitalize the local community's economy. The role of the Department of Industry, Trade, Energy and Mineral Resources (Dinas Perindustrian, Perdagangan, Energi, dan Sumber Daya Mineral/Disperindag ESDM) of North Sumatra Province must be analyzed from a sharia accounting perspective to ensure smoothness and fairness in collecting data on creative industries in Micro, Small and Medium Enterprises (MSMEs) in Medan City. This research aims to analyze the role of the Disperindag ESDM of North Sumatra Province in collecting data on creative industries among MSMEs in Medan using a sharia accounting framework. The method used is literature research to understand the concepts and principles of sharia accounting as well as interviews with other stakeholders in Medan City to understand the practices applied in developing the MSME creative industry. Currently there are several problems in collecting data on Small and Medium Industries (Industri Kecil Menengah/IKM) by the ESDM Department of Industry and Trade of North Sumatra Province. One of them is the difficulty of collecting MSME data in a timely and accurate manner, especially in places that are difficult to reach, so this can affect the quality of the information obtained. However, human resources are still limited to collect and analyze MSME data so that the effectiveness and efficiency of data collection is also disrupted.